Control System Strategy for Ring Thrower Robot Based on PID-CSA for ABU Robocon 2023 - Budiyarto, Aris; Ridwan, Ridwan; Akbar, Rizky Andhika (Universitas Andalas, 2024)
Thrower Robot need to maintain system stability in carrying out their tasks, which require accuracy and stability while throwing the ring in different zones and have different distances and height, so the thrower robot needs to maintain the stability of the system in order to reach target properly. Maintain the stability of the thrower is important because of the physical task like throwing the ring. However, disturbance from external systems can affect the accuracy which can reduce the performance of the robot while performing their task. Therefore, system needs stable accuracy in performing the tasks despite interference. The control system is used to maintain acceleration and elevation in the process of throwing the ring so that it can reach the specified target. The implemented system uses Proportional, Integral and Derivative (PID) control based on the Cuckoo Search Algorithm (CSA). Function of PID control is to maintain a constant position at a certain target and CSA is used to simplify PID control tunning when it has some parameter modifications. Therefore, combination of PID-CSA is applied for this system to produce a control system that aims to maintain stability and reduce disturbances contained in the ring throwing robot based on manipulation. From the result obtained, the PID-CSA method has a better level of stability because it can reduce the percentage value of the error which produced by PID-TE by showing the percentage value of distance error up to 0.68% and value of angle error up to 2.39%.